PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR IPS PESERTA DIDIK DI SMPN 4 SURABAYA - Syafika, Nasrin; Rizal Ma’ruf, Mohammad; Haris Kurniawan, Achmad; Ayu Larasati, Dian; Musrifajaton, Musrifajaton (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was motivated by the low interest and learning outcomes of class VII-F students at SMP Negeri 4 Surabaya. Learning that is not in accordance with students' abilities can cause students to be less active and experience a decrease in interest in learning. Low interest in learning can have an impact on low learning outcomes. This II-cycle research aims to determine whether the application of Teaching at the Right Level (TaRL) can increase student interest and learning outcomes in social studies subjects. This type of research is classroom action research (PTK) using Kurt Lewin's cycle design. The location of this research was at SMP Negeri 4 Surabaya in class VII-F with research subjects of 33 students. The indicator of the success of this research is that there has been an increase in students' interest in learning in various aspects. The mean value increased 19% from 47.75% in cycle I to 66.75% in cycle II. The highest percentage score occurred in the attention indicator, while the lowest occurred in the involvement aspect. In the aspect of learning outcomes, it can be interpreted that the learning outcomes of students in cycle II experienced an increase in percentage at 50% with details of 17 out of 34 students having completed compared to during cycle I, namely there were only 4 students who had achieved the level of completeness of learning outcomes in terms of social studies lessons.